Musculoskeletal disorders of the neck and shoulder in dental hygienists and dental hygiene students. - Morse T; Bruneau H; Michalak-Turcotte C; Sanders M; Warren N; Dussetschleger J; Diva U; Croteau M; Cherniack M (Journal of Dental Hygiene)
PURPOSE: Dental hygienists have been found to have high rates of neck and shoulder disorders, but there is very limited information on risk factors associated with those disorders, the level of risk for students, and the relationship of prior work as dental assistants for dental hygiene students. This study examines self-reported and physician-diagnosed neck and shoulder pain. METHODS: A cohort consisting of 27 dental hygiene students with no prior dental occupation experience (mean age 24, 6.2 SD), and 39 dental hygiene students with prior experience as dental assistants (mean age 28, 6.0) and 94 experienced dental hygienists (mean age 46, 8.8) completed a questionnaire on risk factors and self reported pain, and were examined by a physician in reference to upper extremity findings and diagnoses. Analysis included tabular, trend, and logistic regression analysis. RESULTS: There were significant differences for risks, symptoms, and physician findings. Risk factors had a stepwise progression for students, student/assistants, and experienced dental hygienists, including working with a bent neck often or very often (79%, 89%, 96%, respectively, p<.001), static posture (39%, 50%, 63%, p<.001), precise motions (58%, 67%, 90%, p<.001), and repetition (79%, 86%, 98%, p<.001). Neck symptoms were reported by 37%, 43%, and 72%, respectively (p<.001), and 11%, 20%, and 35% for shoulder symptoms (p<.05). Similar patterns were demonstrated in physician findings, particularly for neck disorders (18%, 36%, 50%, p<.01). In regressions, self-reported shoulder pain was significantly associated with working above shoulder height (OR=1.5, CI 1.0-2.4), and neck symptoms with working with a bent neck (OR=2.1, CI 1.3-3.4), with a protective effect from high supervisor support (OR=0.5, CI 0.2-1.0). CONCLUSION: Risk factors and both self-reported and physician-diagnosed neck and shoulder symptoms increase in frequency from students to experienced hygienists, and students have higher prevalence if they are also dental assistants.